A mathematical analysis of an eco-epidemiological model with prey-feedback effect and prey-refuge (Selecciones Matemáticas, 2025)
This study investigates an eco-epidemiological model incorporating feedback mechanisms and prey refuge, formulated as a system of nonlinear ordinary differential equations. The model describes interactions among susceptible prey, infected prey, and predators, including disease transmisión and nonlinear predation effects. We establish the existence, uniqueness, and positivity of solutions, and analyze their boundedness within a biologically feasible region. Local stability of equilibria is studied via linearization, while global stability is proven using Lyapunov functions. Numerical simulations complement the analytical results, demonstrating how key parameters affect the system’s long-term dynamics.
Keywords: Eco-epidemiological model; Prey refuge; Feedback mechanisms; Stability analysis; Numerical simulations